Spatiotemporal Variations of Vegetation Net Primary Productivity and Its Response to Meteorological Factors Across the Yellow River Basin During the Period 1981–2020 - Tian, Hongwei; Ji, Xingjie; Zhang, Fangmin (Frontiers in Environmental Science, 2022)
Based on trend analysis, partial correlation analysis, and Mann–Kendall test, we analyzed the spatiotemporal variations of net primary productivity (NPP) in the Yellow River Basin and their responses to meteorological factors during the period 1981–2020. The results revealed that NPP had high values in the mid-south part but low values in the northwestern part of the Yellow River Basin. The average NPP was 195.3 g C·m−2·a−1 from 1981 to 2020, and the inter-annual fluctuation of NPP showed a significant increasing trend with an increasing rate of 2.35 g C·m−2·a−2 (p < 0.01). The annual mean temperature showed a positive correlation with NPP in 99.6% of the basin, and 91.4% of which passed the 0.01 significant test. NPP and annual precipitation positively correlated in 87.1% of the basin, and 41.7% of which passed the 0.01 significant test. In 75.2% of the basin, NPP was related negatively with annual sunshine hours, and 17.6% of which of which passed the 0.01 significant test.